The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fnins.2019.00408
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Information Replacement of Working Memory After Sleep Deprivation: Evidence From an Event-Related Potential Study

Abstract: Working memory (WM) components are altered after total sleep deprivation (TSD), both with respect to information replacement and result judgment. However, the electrophysiological mechanisms of WM alterations following sleep restriction remain largely unknown. To identify such mechanisms, event-related potentials were recorded during the n-back WM task, before and after 36 h sleep deprivation. Thirty-one young volunteers participated in this study and performed a two-back WM task with simultaneous electroencep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 42 publications
4
29
1
Order By: Relevance
“…For working memory tasks, the effects of repetitive partial sleep deprivation (PSD) and TSD are not related to the level of execution load, and the effects of PSD are observed to be small ( Lo et al, 2012 ). Although in this study we only selected spatial working memory tasks, sleep deprivation also reduces the quality of information storage in pronunciation working memory ( Zhang et al, 2019 ) and damages the performance of the entire working memory system ( Peng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For working memory tasks, the effects of repetitive partial sleep deprivation (PSD) and TSD are not related to the level of execution load, and the effects of PSD are observed to be small ( Lo et al, 2012 ). Although in this study we only selected spatial working memory tasks, sleep deprivation also reduces the quality of information storage in pronunciation working memory ( Zhang et al, 2019 ) and damages the performance of the entire working memory system ( Peng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced amplitude and sustained latency of the P3 and N2 component are associated with prolonged sobriety ( Koslowsky and Babkoff, 1992 ; Morris et al, 1993 ; Jones and Harrison, 2001 ). A decrease in P3 volatility may reflect a reduction in individual attention and discernment of target stimuli ( Zhang et al, 2019 ). Research in the field of sleep using these techniques has linked TSD with response inhibition and working memory, and shown that working memory would be impaired after TSD.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has demonstrated the critical impairments of SD on various cognitive abilities, especially on working memory both in younger and older healthy adults, after total SD or partial SD [14,15,[39][40][41][42][43]. Behavioral results of almost all these past studies found that subjects showed a significantly lower response accuracy rate, longer reaction time, and higher lapse rate on the working memory test after SD 4…”
Section: Working Memory and Alff Changes After Sdmentioning
confidence: 99%
“…The change to the P2 wave in working memory requirements is also very sensitive ( Smith et al, 2002 ). A study has shown that sleep pressure can significantly reduce the P2 peak amplitude in working memory and increase the latency ( Zhang L. et al, 2019 ). There are two potential reasons for the decrease in P2 peak amplitude: information processing changes and damage to information in early recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most studies have focused on long-term SD; therefore, whether low homeostatic sleep pressure has an adverse effect on individual cognitive processing and changes in the early ERP components has not yet been systematically concluded. Furthermore, there have been inconsistencies among some research findings ( Evans and Federmeier, 2007 ; Wiggins et al, 2018 ; Zhang L. et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%